DISPARITY ANALYSIS OF THE LEARNING PROCESS OF ISLAMIC RELIGIOUS EDUCATION IN BANGKA BELITUNG PROVINCE: APPLICATION OF STATISTICAL PROCESS CONTROL (SPC) - Pratama, Dinar; Azhar, Azhar (International Journal of Business, Law, and Education, 2023)
The problem of disparity in the learning process between Madrasahs is one of the contributors to the low quality of Madrasahs. To get the quality of learning, variability in the learning process needs to be suppressed to a minimum. Variability in the learning process can be in the form of differences in teacher competence, availability of learning facilities or facilities, financial capabilities of Madrasah, and socio-cultural factors of the Madrasah environment. Using a quantitative approach, this study aims to analyze the disparity in the learning process between Madrasah Aliyah (MA) in Bangka Belitung Province based on the achievement of UAMBN scores. Data analysis using the Statistical Processes Control (SPC) method with statistical techniques T2. The SPC method generates a control chart that will be used to determine if there is a disparity among Madrasah. The results of data analysis show that there is a disparity in the learning and teaching process at MA in Bangka Belitung Islands Province based on UAMBN's achievements in three subjects (Qur'an Hadith, Fiqh, and Islamic Cultural History). Some things that can be done by related parties to reduce disparities are, 1) coaching all human resources (teachers and education staff) gradually, 2) equitable distribution of the number and quality of teachers, both in public and private, 3) controlling the admission of prospective students so that there is no inequality of interest, and 4) striving for proportional distribution of financial aid for each MA.